Waldungen : Die Deutschen und Ihr Wald. - Weyergraf, Bernd; Fischer, Hubertus; Tournier, Michel; Roters, Eberhard; Mattenklott, Gert; Budde, Elmar; Hürlimann, Annemarie; Rothe, Friedrich; Graf, Volker; Graf, Werner; Plessen, Marie - Louise; Graefe, Rainer; et al. (Berlin : Nicolaische Verlagsbuchhandlung, 1987)
Achenbach, Andreas ; Appelt, Dieter ; Armando ; Arp, Hans ; Badura, Michael ; Baselitz, Georg ; Becker, F. ; Becker, Peter ; Bendemann, Eduard ; Beuys, Joseph et al.
Waldungen : Die Deutschen und Ihr Wald, Akademie der Künste, Berlin, vom 20. September bis 15. November 1987
kunstcatalogus